Vertical integration in service industries: an exploratory study at the healthcare industry in São Paulo Integração vertical nas operadoras de assistência médica privada: um estudo exploratório na região de São Paulo - Gustavo M. de Albuquerque; Maria Tereza Leme Fleury; André Leme Fleury (Production)
Different production arrangements have been experienced in several economic fields. It is possible to observe integration cycles, when a company becomes responsible for consecutive stages in the production chain of goods and services. This process, known as vertical integration, generates many implications that have been analyzed by studies about operational management, transaction costs economics, competition and anti-trust regulation. Focused on the healthcare industry, this research aims to analyze the managerial perception about vertical integration in this field, aiming to gain insights about the motivations and implications of this process, not sufficiently exploited by the specialized literature. Using a qualitative approach, interviewees were asked to rank possible vertical integration benefits. It was noticed that the control of production costs and the optimization of services' quality were the main benefits of this process. Obtained results reinforce some perceptions gained at studies conducted among north american companies; however, some differences were observed, which are characteristic of the analyzed context. Arranjos produtivos têm sido feitos em diferentes setores da economia, resultando em ciclos de integração quando uma empresa torna-se responsável por etapas consecutivas da cadeia de produção de bens e serviços. Esse processo, denominado integração vertical, apresenta implicações diversas, exploradas em estudos sobre operações industriais, economia dos custos de transação, competitividade e políticas antitruste. Este estudo tem como foco o setor de saúde e objetiva levantar a percepção de gestores do setor de assistência médica privada sobre esse movimento de integração vertical, suas motivações e implicações. Através de pesquisa qualitativa realizada com gestores de empresas de saúde sobre os possíveis benefícios da verticalização, observou-se que o controle dos custos de produção e a melhoria da qualidade ou resolutividade dos serviços médicos são os principais benefícios obtidos com esse processo. Os resultados corroboram em parte os de pesquisas realizadas no contexto norte-americano, porém também identificam dimensões diferentes, características do cenário analisado.